AeroMAPS: a framework for performing multidisciplinary assessment of prospective scenarios for air transport - Planès, Thomas; Delbecq, Scott; Salgas, Antoine (Journal of Open Aviation Science, 2023)
AeroMAPS is an open-source software, also available as a web application, for performing multidisciplinary assessment of prospective scenarios for air transport. Such investigations are a significant challenge for aviation stakeholders but are required to explore and evaluate different transition strategies for the sector. The framework presented in this paper aims to provide these stakeholders with a standardised methodology for simulating prospective scenarios. Developed using the Python programming language and easy to use via Jupyter Notebooks or graphical user interfaces, it enables the rapid exploration of various decarbonisation strategies for research or decision-making audiences. Several scientific computing packages are used to facilitate the modular assembly of models and solve complex numerical problems. The framework is structured around various models derived from the academic literature and newly developed ones. In particular, it can be used to model various components of the air transport system (air traffic, aircraft fleet, energy carriers), assess its environmental (climate and energy resources) and cost impacts, and perform environmental sustainability analyses. An application is proposed in this paper in order to understand the capabilities, interests and limits of the software. Future developments are planned to improve existing models, complete environmental analyses and continue extending to other disciplinary fields (economics, regulation, sociology), in order to make AeroMAPS a systemic and holistic aviation integrated assessment model.